Fitness-for-service assessment for pressurized components - Ji, Jonathan Jia Yang (2010)
Fitness-for-Service (FFS) is a widely used assessment procedure to determine if pressurized equipment is qualified for continual service. The outcome of this assessment includes continual service, repair, or to retire the equipment. By using this assessment, a high level of safety could be achieved. There are in total 3 Levels of Assessment. Level 1 Assessment is the basic screening assessment where minimum geometric and material information of the pressurized equipment is required. The higher level of Assessment requires more data and is deemed to be more accurate and requires a lower level of safety margin. If a component does not pass the first Level, it will proceed on to the following level. FFS is based on the American Petroleum Institute (API) Recommended Practice (RP) 579.